2020
DOI: 10.1029/2019ms002020
|View full text |Cite
|
Sign up to set email alerts
|

Tropical Cyclogenesis From Self‐Aggregated Convection in Numerical Simulations of Rotating Radiative‐Convective Equilibrium

Abstract: In a modeled environment of rotating radiative-convective equilibrium (RCE), convective self-aggregation may take the form of spontaneous tropical cyclogenesis. We investigate the processes leading to tropical cyclogenesis in idealized simulations with a three-dimensional cloud-permitting model configured in rotating RCE, in which the background planetary vorticity is varied across f -plane cases to represent a range of deep tropical and near-equatorial environments. Convection is initialized randomly in an ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 53 publications
5
16
0
1
Order By: Relevance
“…The leading contribution from longwave radiation to the increase of CIMSE within the circulation center at the early stage of simulations indicates that longwave radiation may be the primary factor in regulating TC genesis. This conclusion is consistent with previous modeling studies which suggested that longwave radiation is the leading contributor for tropical convective systems at their early stage (Carstens & Wing, 2020;Muller & Romps, 2018;Smith et al, 2020;Wing & Cronin, 2016;Wing & Emanuel, 2014…”
Section: Model Simulationssupporting
confidence: 93%
See 1 more Smart Citation
“…The leading contribution from longwave radiation to the increase of CIMSE within the circulation center at the early stage of simulations indicates that longwave radiation may be the primary factor in regulating TC genesis. This conclusion is consistent with previous modeling studies which suggested that longwave radiation is the leading contributor for tropical convective systems at their early stage (Carstens & Wing, 2020;Muller & Romps, 2018;Smith et al, 2020;Wing & Cronin, 2016;Wing & Emanuel, 2014…”
Section: Model Simulationssupporting
confidence: 93%
“…Accordingly, simulations in HOM_RA show less likelihood of TC genesis and slower intensification rates, indicating that removing cloud-radiative interactions suppresses TC development. The higher percentage of TC genesis events in CTL is consistent with previous modeling studies which suggested that cloud-radiative interactions play a crucial role in promoting tropical cyclogenesis (Carstens & Wing, 2020;Muller & Romps, 2018;Smith et al, 2020;Yang & Tan, 2020).…”
Section: Model Simulationssupporting
confidence: 91%
“…Such "rotating RCE" simulations allow for an investigation of fundamental controls on TC formation, absent complications from other disturbances, varying environmental conditions, or surface heterogeneities. The formation of individual TCs has been investigated in this setting (Boos et al, 2016;Carstens & Wing, 2020;C. A. Davis, 2015;Muller & Romps, 2018;Ramsay et al, 2020;Yang & Tan, 2020;Wing et al, 2016), as have the statistics of a population of TCs ("TC world"; Cronin & Chavas, 2019;Held & Zhao, 2008;Khairoutdinov & Emanuel, 2013;Reed & Chavas, 2015;Zhou et al, 2014Zhou et al, , 2017.…”
Section: Idealized Modelingmentioning
confidence: 99%
“…When RCE simulations include rotation, TCs spontaneously develop. TC genesis, intensification, and structure have been studied using a variety of RCE model configurations, including small, f-plane domains that contain single TCs (e.g., Carstens & Wing, 2020;Knutson & Tuleya, 2004;Nolan et al, 2007;Ramsay et al, 2020; and larger domain simulations with multiple TCs (e.g., Chavas & Emanuel, 2014;Held & Zhao, 2008;Zhou et al, 2014). However, these model configurations simulate TCs on a flat, cartesian surface and therefore do not include the impacts of Earth's spherical geometry on TCs, namely the beta effect (Chan, 2005;Merlis & Held, 2019).…”
Section: 1029/2021jd035197mentioning
confidence: 99%